An Assessment of Resource-Based Theorizing on Firm Growth and Suggestions for the Future. (January 2018) - Nason, Robert S.; Wiklund, Johan
Together, Penrosean and Barnean resource-based logic make up the dominant theoretical approach to understanding firm growth. While extant literature focuses on a common lineage between Penrosean theory and the resource-based view (RBV), we explicate divergence at these origins of resource-based theorizing and subject the growth implications of each to meta-analytic testing. RBV's central tenets concern resources that meet valuable, rare, inimitable, and nonsubstitutable (VRIN) criteria, while Penrose's theory discusses the versatility of resources. Theoretically, VRIN resources allow firms to exploit unique opportunities, while versatile resources allow firms to recombine resources in novel ways to create growth. Using meta-analytic techniques, we find that versatile resources are associated with higher levels of growth, whereas VRIN resources are not. We offer novel insights into alternative characteristics of resources derived from the same conceptualization of the firm, add greater specificity to the performance construct, and open up avenues for new theorizing on firm growth that is more closely aligned with Penrose's theory.